2018
DOI: 10.1083/jcb.201804205
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy in intestinal stem cells promotes gut dysplasia in Drosophila

Abstract: Aneuploidy is associated with different human diseases including cancer. However, different cell types appear to respond differently to aneuploidy, either by promoting tumorigenesis or causing cell death. We set out to study the behavior of adult Drosophila melanogaster intestinal stem cells (ISCs) after induction of chromosome missegregation either by abrogation of the spindle assembly checkpoint or through kinetochore disruption or centrosome amplification. These conditions induce moderate levels of aneuploi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…However, in contrast to imaginal cells, ISCs do not undergo apoptosis and, instead, overproliferate causing the formation of tissue dysplasia [23,25]. ISCs are resistant to apoptotic signalling, and this may be central explaining the pro-tumorignic role of JNK in this specific cellular context [25,38]. In agreement with this, cultured mammalian embryonic stem cells tolerate aneuploidy and polyploidy without undergoing apoptosis [39].…”
Section: Chromosome Instability In Stem Cellsmentioning
confidence: 85%
See 2 more Smart Citations
“…However, in contrast to imaginal cells, ISCs do not undergo apoptosis and, instead, overproliferate causing the formation of tissue dysplasia [23,25]. ISCs are resistant to apoptotic signalling, and this may be central explaining the pro-tumorignic role of JNK in this specific cellular context [25,38]. In agreement with this, cultured mammalian embryonic stem cells tolerate aneuploidy and polyploidy without undergoing apoptosis [39].…”
Section: Chromosome Instability In Stem Cellsmentioning
confidence: 85%
“…This approach also reveals that fly neoplasms show GIN and accumulate SNPs as well as CNVs that are in the range of human cancers [ 172 ]. Additionally, ISCs have been helpful in the study of stem cells and an analysis of ageing in adult flies [ 25 , 138 ] ( figure 4 c ).
Figure 4.
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite fittingly, it was recently reported that aneuploidy in Drosophila Intestine Stem Cells (ISCs) results in increased stem-cell proliferation. Interestingly, ISCs do not activate apoptotic pathways in response to aneuploidy, suggesting that this type of cell is somewhat resistant to genomic imbalance [62]. Unusual resistance to altered ploidy was also observed in human and mouse embryonic stem cells (ESCs), mostly achieved by relaxing the cell-cycle control and uncoupling the spindle checkpoint from apoptosis [63].…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila midgut ISC mitosis is controlled by key signaling pathway ligands, including Delta, upd1-3, vein, dilp3,6 and eiger (Doupe, 2018), but mitosis can be diverted towards dysplasia due to deregulation of many of the same signaling pathways these ligands may control (Apidianakis 2009;Biteau 2008). Adult midgut dysplasia in Drosophila has been characterized by the widespread, irreversible and progressive loss of proper cell differentiation due to accumulation of groups of ISC-like and EE cells (Apidianakis, 2009;Biteau, 2008;Resende, 2018), and it is to be contrasted with the rare ISC-like/EE large tumors caused by spontaneous loss of heterozygosity of notch in old flies (Siudeja, 2015). A common property of differentiating Drosophila cells that need to cope with tissue development and homeostasis is endoreplicative cell growth.…”
Section: Introductionmentioning
confidence: 99%